The Development of the Two-Tier Diagnostic Test Instrument with Google Form to Measure Student Misconceptions on Energy and Energy Forms - Pratiwi, Ika Thalia; Viyanti; Permadi, Dimas (Impulse: Journal of Research and Innovation in Physics Education, 2024)
This study develops a two-tier diagnostic test instrument with Google Forms- to measure student misconceptions about energy and energy forms. The development research used the 4-D model with 4 stages: (1) define; (2) design; (3) develop; and (4) disseminate. The researchers validated the product to evaluate the construct, material, and language aspects. Expert validation results declared the two-tier diagnostic test instrument very valid at 87.7%. The researchers tested the two-tier diagnostic test instrument with Google form to measure student misconceptions on 30 students and then analyzed using the Rasch model with the assistance of Ministep 5.6.2 software. Based on the results of the Rasch analysis, 20 valid items were obtained. The questions on the two-tier diagnostic test instrument to measure student misconceptions were reliable, with a Cronbach alpha value of 0.66, categorized as adequate. The final product of the developed instrument met the standards of instrument validity and reliability.